Three Studies: Use of Family Living News - Terence L. Day (Journal of Applied Communications, 1979)
No question is more pervasive among news communications professionals in the agriculture information offices of the nation's land-grant universities than this: Are information office programs in harmony with the needs of the various print and electronic media?